Stress fractures in football. Issue 4 (23rd June 2016) - Dhillon, Mandeep S; Ekstrand, Jan; Mann, Gideon; Sharma, Siddhartha
Abstract : Football (soccer) is one of the most popular sports in the world with high-reported injury rates; many injuries are potentially career ending. Stress fractures represent the inability of a normal or weakened bone to withstand repeated stresses and are reported to account for 0.5% of all football-related injuries. The pathophysiology of stress factors is multifactorial and involves a complex interplay of several extrinsic and intrinsic factors. A high degree of suspicion and adequate imaging is necessary to diagnose these injuries, as plain radiographs may miss the diagnosis in many cases. Once the diagnosis of a stress fracture has been confirmed, treatment consists of activity modification and relative or complete rest, depending on the site and nature of the stress fracture. Surgical intervention may be necessary in the 'high-risk' stress fractures, which are prone to displacement, delayed union and non-union. This review looks at the epidemiology, aetiopathogenesis, classification, diagnosis and treatment of stress fractures in football.